Salivary cues: simulated roe deer browsing induces systemic changes in phytohormones and defence chemistry in wild‐grown maple and beech saplings. (8th August 2016) - Ohse, Bettina; Hammerbacher, Almuth; Seele, Carolin; Meldau, Stefan; Reichelt, Michael; Ortmann, Sylvia; Wirth, Christian
Summary: Tree saplings in temperate forests world‐wide experience intense browsing from deer and other mammalian herbivores. However, when compared to insect herbivory, our knowledge about the cues that trigger mammalian‐induced defence responses in trees is limited. We studied responses of field‐grown saplings of European beech ( Fagus sylvatica L.) and Sycamore maple ( Acer pseudoplatanus L.) to simulated browsing by (i) clipping apical buds or leaves and (ii) additionally applying roe deer ( Capreolus capreolus L.) saliva to the cut surface. We analysed induced changes in phytohormones and phenolics in the saplings' remaining buds or leaves, respectively. In both species, jasmonates were activated after clipping of buds and leaves. Importantly, additional saliva application activated salicylic acid in beech leaves and led to increases in cytokinins in beech buds. Saliva application also led to an increased biosynthesis of several hydrolysable tannins (mainly ellagitannins) and flavonols in maple leaves. Condensed tannins, the most abundant phenolics in beech buds and leaves, did not change after either clipping or saliva application. However, clipping with additional saliva application decreased levels of phenolic acids (cinnamic acid derivatives) in beech buds. We conclude that the two tree species perceive and respond to unknown elicitors in the deer saliva, resulting in changes in phytohormone levels and defence‐associated secondary metabolites. We suggest that variation in induced defence responses between tree species as well as between buds and leaves is related to differences in morphological traits, which interrelate with chemical traits and result in species‐specific strategies to respond to mammalian herbivory. Abstract : Lay Summary